Successful endovascular treatment of recurrent venocorporeal erectile dysfunction using a liquid non-adhesive embolizing agent "KAP". Case report - D. G. Ioseliani; A. G. Koledinskiy; S. P. Semitko; L. M. Rapoport; D. A. Asadov; N. V. Petrovskii; K. V. Gyulmisaryan; V. V. Fomenko; S. A. Kibets; I. E. Chernysheva; P. V. Glybochko (Consilium Medicum)
According to the Russian Society of Urologists, almost half of the male population of the country aged 27 to 77 suffers from erectile dysfunction (ED). ED should be considered not only as a serious medical nosology, but also as an important socio-psychological problem of national importance due to its demographic significance. There are many methods of treating ED, including drug therapy and penile prosthetics, as well as certain psychotherapeutic measures. The world's experience in combating this disease allows us to assert that an important condition for determining the correct approach to treating ED is an accurate diagnosis of the causes of ED. Among the many causes of ED, vascular causes are quite common. Given the rapid development of endovascular and low-traumatic approaches to vascular pathology, the method of improving the inflow and obstructing the outflow in vasculogenic ED is becoming increasingly obvious and effective. The presented article discusses a clinical case of successful endovascular complex treatment of recurrent venocorporeal ED in a young patient.